Dialog Epistemik dan Pengabaian Agensi Bumiputra dalam De Indische Mercuur tentang Wabah Belalang di Jawa (1916-1917) - Ardhiatama Purnama Aji (Journal of Indonesian History, 2026)
Javanese grasshopper (Valanga nigricornis) attacks in Java during 1913-1917 were not merely ecological disasters, but rather catalysts for complex epistemic debates among colonial elites in the pages of De Indische Mercuur. Through intertextual analysis, this research reveals how the epistemic positions of the key actors: Dr. W. Roepke (entomologist), J. Th. White (agricultural expert), G. J. Vink (agricultural extension officer), and L. E. Dom van Rombeek (administrator) were shaped not by individual preferences, but by institutional thinking and relations of power in knowledge production. The debate, reflecting contestation between Roepke's biological determinism and White's agronomic solutionism, exposes structural gaps between science and field practice. The politics of representation in this dialogue reveals tensions between the interests of large-scale plantation economies (coffe and rubber) and small-scale peasant economies (coconut, corn, and cassava). Analysis of White's boundary work demonstrates attempts to claim epistemological autonomy for agronomy through empirical field evidence. Paradoxically, despite both sides acknowledging the effectiveness of local peasant practices, colonial knowledge narratives consistently excluded the agency and local knowledge of Bumiputra peasants, transforming the mobilization of peasant labor into mere extractive labor without recognition of their intellectual contributions. This research demonstrates that fragmentation of colonial knowledge was not simply academic epistemic anxieties, but rather a manifestation of systematic epistemological hegemony.